Development of research skills in nursing students: New challenges in the training context - Rojas Salazar, Arcelia O. (2019)
The development of research skills is a necessity because the research is one of the substantive processes in the university, but it represents a function in the professional profile, the nursing graduate, and knowledge generation and problem solving. Method, a quasi-experimental design with two groups and with measurement only after the application of the educational program. The sample consisted of 24 fourth-year nursing students, for the experimental group; and 24 students for the control group. The data collection was used as direct observation technique; and as instruments, an evaluation guide for the research skills of conceptual, procedural and attitudinal construction, procedural, attitudinal construction and the evaluation of the educational program. The Student's T test was used to the examination of the hypothesis to the independent samples. For the statistical significance was used the reliability of 95%, and a margin of error of 0.05. The results in the application of the educational program was 79.2%, magnitude of the effect; in the experimental group presented advanced level in research skills compared to 20.8% of the control group with medium level research skills; statistically significant differences were found in the scores between the two groups for the research skills in general; and according to conceptual, procedural and attitudinal construction skills dimensions, all with p≤0,000. In conclusion, the educational program has positive effectiveness in the development of research skills in fourth-year nursing students.